Is there a Publication Bias in Behavioural Intranasal Oxytocin Research on Humans? Opening the File Drawer of One Laboratory. (25th April 2016) - Lane, A.; Luminet, O.; Nave, G.; Mikolajczak, M.
Abstract : The neurohormone oxytocin (OT) has been one the most studied peptides in behavioural sciences over the past two decades. Primarily known for its crucial role in labour and lactation, a rapidly growing literature suggests that intranasal OT (IN‐OT) may also play a role in the emotional and social lives of humans. However, the lack of a convincing theoretical framework explaining the effects of IN‐OT that would also allow the prediction of which moderators exert their effects and when has raised healthy skepticism regarding the robustness of human behavioural IN‐OT research. Poor knowledge of the exact pharmacokinetic properties of OT, as well as crucial statistical and methodological issues and the absence of direct replication efforts, may have lead to a publication bias in the IN‐OT literature, with many unpublished studies with null results remaining buried in laboratory drawers. Is there a file drawer problem in IN‐OT research? If this is the case, it may also be true in our own laboratory. The present study aims to answer this question, document the extent of the problem and discuss its implications for OT research. For eight studies (including 13 dependent variables overall, as assessed through 25 different paradigms) performed in our laboratory between 2009 and 2014 on 453 subjects, the results obtained were too often not those that were expected. Only five publications emerged from our studies and only one of these reported a null finding. After realising that our publication portfolio has become less and less representative of our actual findings and because the nonpublication of our data might contribute to generating a publication bias in IN‐OT research, we decided to retrieve these studies from our drawer and encourage other laboratories to do the same.